The role of Epstein-Barr virus in multiple sclerosis: from molecular pathophysiology to in vivo imaging - Guan, Yi; Jakimovski, Dejan; Ramanathan, Murali; Weinstock-Guttman, Bianca; Zivadinov, Robert (Neural regeneration research, 2019)
Multiple sclerosis (MS) is a disease of the central nervous system characterized by inflammation, demyelination, and neuronal damage. Environmental and genetic factors are associated with the risk of developing MS, but the exact cause still remains unidentified. Epstein-Barr virus (EBV), vitamin D, and smoking are among the most well-established environmental risk factors in MS. Infectious mononucleosis, which is caused by delayed primary EBV infection, increases the risk of developing MS. EBV may also contribute to MS pathogenesis indirectly by activating silent human endogenous retrovirus-W. The emerging B-cell depleting therapies, particularly anti-CD20 agents such as rituximab, ocrelizumab, as well as the fully human ofatumumab, have shown promising clinical and magnetic resonance imaging benefit. One potential effect of these therapies is the depletion of memory B-cells, the primary reservoir site where EBV latency occurs. In addition, EBV potentially interacts with both genetic and other environmental factors to increase susceptibility and disease severity of MS. This review examines the role of EBV in MS pathophysiology and summarizes the recent clinical and radiological findings, with a focus on B-cells and in vivo imaging. Addressing the potential link between EBV and MS allows the better understanding of MS pathogenesis and helps to identify additional disease biomarkers that may be responsive to B-cell depleting intervention.